Comparison of neurocognitive deficit among euthymic bipolar I disorder patients, their first-degree relatives and healthy controls - Gowda, Sunil N.; Chandak, Sumit; Sawant, Vishal; Kulkarni, Amit (International Journal of Advances in Medicine, 2017)
Background: Bipolar patients often suffer from debilitating cognitive impairment in different stages of the disease (manic, depressive or euthymic states). We assessed and compared the frequency of neurocognitive deficit among individual with bipolar I disorder but currently in euthymic state, their first-degree blood relatives and healthy controls. In addition, we also probed further into the type of neurocognitive deficit that can be seen among them and observed the influence of sociodemographic characteristics with the occurrence of neurocognitive deficit in individual with bipolar I disorder patient. Methods: Patients (N=30) who fulfilled the diagnostic and statistical manual of mental disorders, fourth edition (DSM-IV TR) criteria for bipolar I disorder but currently in remission were assessed for any neurological deficits using the standard instruments. In this study, 30 first-degree blood relatives of bipolar I disorder patients and selected 30 hospital staff as healthy controls were also assessed for neurological deficits. Results: We did not find any significant frontal dysfunction among first-degree blood relatives of bipolar I disorder patient when compared with euthymic bipolar I disorder patients. Factor that significantly affected neurocognitive performance in the bipolar patients who were in euthymic state included age, total duration of illness and number of manic episode. Conclusions: As neurocognitive impairment is associated with number of manic episode and total duration of illness; the objective of treatment should be to prolong remission and impart psychoeducation regarding nature of illness. On the contrary, anticipating definite cognitive impairment in first-degree blood relatives of bipolar I disorder patient when compared to healthy control warrants periodic neurocognitive testing and psychoeducation about deficit and medical intervention, if required.